Pro JavaScript with MooTools - Obcena, Mark (Apress : Imprint: Apress, 2010)
Pro JavaScript with MooTools is unlike any other JavaScript book on the market today. While similar books focus on either JavaScript as a language of the browser or how to use JavaScript frameworks, Pro JavaScript with MooTools fills the gap between these topics and moves beyond-exploring the advanced features of JavaScript and how the MooTools framework uses these features to further improve the language itself. The book itself takes a unique three-pronged approach. It first walks you through the advanced features of JavaScript and the MooTools framework, including native augmentation and type creation, a comprehensive discussion of JavaScript functions, object-oriented programming with native JavaScript and MooTools Classes, and the MooTools Class internals. You'll then learn all about Javascript in the DOM: the Elements classes and its internals, the MooTools Event system, Selector engines and MooTools Slick, Ajax and the Request Object, and animation and the Fx classes. The final section really sets the book apart from all others, as it discusses JavaScript outside the browsers. You'll take an in-depth look at CommonJS and MooTools, using MooTools outside the browser to build ORM, creating simple CommonJS applications via the MooTools Deck framework, and creating complex server-side applications using Raccoon.